Ethno-Digital Ethic Values in Campus Habituation for Strengthening Communication Ethics and Social Trust of Students - Saddam Saddam; Maemunah Maemunah; I Made Putra Suryantara (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
There are still many students who do not fully understand the ethics of digital communication, as can be seen from the way digital communication is not ethical for students to lecturers through WhatsApp shared by private campuses in Mataram City. On the other hand, the concern of campus institutions about this is still not optimal, causing the increasing prevalence of unethical digital communication between students and lecturers. The purpose of the research is to explore and examine the integration of ethno-digital ethic values that can be applied in campus habituation, as well as its influence on strengthening communication ethics and social trust of students in Mataram City. The research method to be used is a mixed method with a concurrent triangulation design. The location of the research is in Mataram City. This research was conducted by involving 157 informants and respondents consisting of 132 students, 10 education staff, 10 lecturers, and 5 campus leaders from five universities in Mataram City. This research was carried out in several stages, initial and follow-up observation, tests, and analysis. The results of the study show that ethno-digital ethic values integrated into campus habituation through academic and non-academic activities have a positive impact on strengthening communication ethics and social trust among Mataram City students. The integration of traditional ethical values with digital norms not only provides a strong moral framework for students but also creates a more inclusive and trusting social climate.